Lateral Position versus Prone Position for Cervical Laminoplasty: A Retrospective Comparative Study - Du L; Gao Y; Gao K; Yang G; Gao S (Dove Medical Press, 2020)
Lin Du, 1, 2 Yanzheng Gao, 1 Kun Gao, 1 Guang Yang, 1 Shanjun Gao 2 1Department of Spine Surgery, Henan Provincial People’s Hospital, People’s Hospital of Zhengzhou University, Zhengzhou City, Henan Province, People’s Republic of China; 2Microbiome Laboratory, Henan Provincial People’s Hospital, People’s Hospital of Zhengzhou University, Zhengzhou City, Henan Province, People’s Republic of ChinaCorrespondence: Yanzheng Gao; Kun GaoDepartment of Spine Surgery, Henan Provincial People’s Hospital, People’s Hospital of Zhengzhou University, 7 Weiwu Road, Zhengzhou City, Henan Province 450000, People’s Republic of ChinaTel +86 13783505855; +86 13838372271Fax +86 0371 65964376Email doctorgao63@163.com; gaokunhigh@126.comPurpose: To examine the safety of lateral decubitus positions for cervical laminoplasty.Patients and Methods: A retrospective comparative study was conducted on the safety between the lateral and prone positions in cervical laminoplasty. After screening, 466 patients who underwent cervical laminoplasty at a single medical center were enrolled and categorized into the lateral (n=229) and prone (n=237) groups. Data on positioning time, surgical time, blood loss, complication rates, and surgical outcomes were collected and compared between the two groups. The patients were further divided into underweight, normal weight, overweight, and obesity subgroups according to their body mass index, and the collected data were compared between the lateral and prone groups.Results: The lateral group had a lower incidence of facial pressure ulcers (2.18%) than the prone group (11.39%). However, positioning time, surgical time, blood loss, and surgical outcomes were not significantly different between the two groups. In the subgroup analysis, no significant difference in positioning time, operative time, and blood loss was observed in the underweight, normal weight, and overweight patients between the two groups, but in the obesity subgroup, the lateral group had a significantly shorter positioning time (15.23± 6.44 vs 21.63± 9.43 min, P=0.045) and operative time (140.16± 40.48 vs 178.62± 51.82 min, P=0.037) and lesser blood loss (285.31± 171.75 vs 430.46± 189.84 mL, P=0.044) than the prone group.Conclusion: The lateral position is as safe as the prone position for cervical laminoplasty, but it has advantages over the prone position for patients with obesity.Keywords: lateral position, prone position, laminoplasty, cervical myelopathy